OPTIMIZATION OF THERMAL PERFORMANCE IN MICROCHANNEL HEAT SINKS USING NANO FLUIDS AND AI-BASED FLOW CONTROL SYSTEMS - Muhammad Aqeel,; Zhao Xianrui,; Zhao Hong-Quan,; Zhang Ling, (Spectrum of Engineering Sciences, 2025)
Introduction The optimization of thermal performance of microchannel heat sinks is important to improve the efficiency of cooling systems in electronics and industrial cooling applications. Nanofluids, i.e. fluids If you have windows XP) Fluids that have been enhanced with nanoparticles have achieved much research interest because of their enhanced heat transfer capabilities. Furthermore, employing AI-based flow control systems, like reinforcement learning, could introduce a new degree of freedom for online optimization of heat sink systems. Objectives: The main goal of this work is to examine the thermal performance of the microchannel heat sinks for the applications of the nanofluids (Al2O3, TiO2 and CuO) under various volume fractions optimized with AI based flow control to improve the heat transfer efficiency with the reduced rate of energy utilization and pressure drop. Method: The microchannel heat sink experiment and were used to experimentally characterize the nanofluids with various volume fractions. The flow rates and pressure drops were measured and the thermal performance was analyzed based on Nusselt number, thermal resistance and heat transfer coefficient. Reinforcement learning algorithms for autonomous control based on AI were used for the real-time control on the flow rate. Computational fluid dynamics (CFD) simulations were also performed to compare with experiment. Results: It was found that nanofluids enhanced the heat transfer whether were more effective than base fluids, Al₂O₃ having gave best performance. The thermal efficiency was optimized by AI-driven flow control, which decreased the temperature by 12.3 °C and the pressure drop by 110 Pa compared with fixed flow rate systems. Nusselt numbers were the CFD simulations performed with good accuracy in the predictions having error of using 2.1%. Conclusions: The joint use of nanofluids and AI-based flow controls systems can be considered an efficient and compact technology for improving the thermal performance of microchannel heat sink, thus making it a promising cooling solution for the new century's applications.